Sistem Untuk Menentukan Pilihan Pada Program Studi Menggunakan Fuzzy Multiple Attribute Decision Making (FMADM) Dengan Simple Additive Weighting (SAW) (Studi Kasus: POLTEKES Permata Indonesia Yogyakarta) - Citrasari Nirsam Priatni (Faculty of Computer Science, University of Jember, 2017)
To continue with higher education students should be able to choose the right course of study in order to continue their studies according to their abilities. This study program is intended for later students can finish college according to their interests and abilities. The process of choosing the current study program has the disadvantage that it takes quite a long time and also the results obtained accurately because it can be a lot of mistakes because there is no special application to support the calculation. In addition, the element of subjectivity was quite high because the criteria yan used is still a little and less relevant. To overcome these problems then made a decision support system to assist Academic Lecturers and Student Affairs in determining the selection of study programs.In this research using Fuzzy MultipleAttribute Decesion Making method with Simple Additive (SAW). The criteria used are the final score of mathematics, the final score of Indonesian language, the final grade of English school, the final value of the school of science. Final Physics School Value, Final Value of Chemistry School, Final Value of Art School's End School of Culture, Final Value of Sports School. End of School Economics Value, End of School Sociology Value, End of School History Value. The end result of this research found that decision support system with SAW method able to overcome the problems in the selection process of study program in high collateral.The calculation result using POLTEKES Permata Indonesia Yogyakarta method and using FMADM method with SAw method have 76.92% match and 23.08% unsuitable data from 26 data in selection of study program. From this research is expected to add knowledge for students and lecturers so that the diagnostic process in determining the study program becomes easy it will simplify the decision making to determine the appropriate study program.